A green vapor suppressing agent for aqueous ammonia carbon dioxide capture solvent: Microcontactor mass transfer study. (1st April 2022) - Rashidi, Hamed; Rasouli, Parvaneh; Azimi, Hossein
Abstract: Aqueous ammonia is a promising carbon dioxide capture solvent and has recently attracted significant attention, but its main problem is high evaporation rate of ammonia in the absorber. Glycerol, which is a by-product of biodiesel, has hydroxyl groups that bind to ammonia molecules. Hence, it can reduce the vaporization of ammonia as an additive and improve the CO2 absorption properties. In this work, the mass transfer performance of glycerol, as an ammonia vaporization reduction additive, was investigated. Carbon dioxide absorption experiments using ammonia-glycerol hybrid solvent have been done in a T-shaped microchannel. The impact of process condition, including ammonia concentration (4–10 wt%), glycerol concentration (1–3 wt%), liquid flow rate (3–9 ml/min) and temperature (20–40 °C) was investigated on the volumetric overall mass transfer coefficient ( K G a V ), absorption percentage (AP) and volumetric molar flux ( N A a V ). According to the results, rising the glycerol concentration in the range of 2–3 wt% leads to an increase in K G a V by 4.8%. Hence, the addition of glycerol to aqueous ammonia not only increases the mass transfer coefficient but also reduces the vapor pressure of ammonia as a green vapor suppressing agent and diminishes the ammonia loss in the absorption tower. Highlights: Ammonia-glycerol hybrid solvent evaluated for CO2 capture. Mass transfer performance of solvent assessed in T-shaped microchannel. Box-Benhken method used to design the experiments and analysis of the results. Higher K G a V values in microchannel reactor compared to other operating units.